Respect Is Central: A Critical Review of Implementation Frameworks for Continuous Quality Improvement in Aboriginal and Torres Strait Islander Primary Health Care Services - Michelle Redman-MacLaren; Nalita Nungarrayi Turner (Anmatyerre/Jaru); Judy Taylor; Alison Laycock; Kristina Vine; Quitaysha Thompson (Gurindji); Sarah Larkins; Karen Carlisle; Sandra Thompson; Ross Bailie; Veronica Matthews (Quandamooka) (Frontiers Media S.A., 2021)
Background: Primary health care (PHC) services are complex systems, shaped by an interplay of factors at individual, organisational and broader system levels. For Aboriginal and Torres Strait Islander PHC services, closer relationships with the people they serve, local knowledge of community, and cultural awareness are critical. Continuous quality improvement (CQI) has proven to be an effective process for identification of priority issues in health care delivery and for instigating the design, implementation and evaluation of improvement interventions in these settings. However, wide-scale variation in care quality persists partly due to the mismatch between CQI interventions and context.Methods: This critical review of implementation frameworks for CQI in Aboriginal and Torres Strait Islander primary health care was conducted in two phases: (1) a review of primary published implementation frameworks used in PHC contexts, and (2) a comparison of key features of these frameworks with quality concepts identified by high-improving Aboriginal and Torres Strait Islander PHC services in remote Australia.Results: We found nine primary implementation frameworks previously used in PHC contexts guiding interventions within and between macro (broader contextual) level; meso (health service) level; and micro (community and inter-personal) level systems. There was commonality between these frameworks and key quality concepts in Aboriginal and Torres Strait Islander PHC. However, none of the frameworks covered all concepts with rare consideration of communities driving health improvement, two-way learning (integrating cultural knowledge into healthcare provision), and caring staff-engendering trusting relationships with community enacted through respect.Conclusion: Respect, as a secret essence, privileges the importance of culture, and is an essential element of CQI implementation frameworks for positive change in Aboriginal and Torres Strait Islander PHC services. It is essential to work with communities to design workforce models that grow a caring stable workforce to ensure improvements in quality of care that are effective for their context.